Studying methods of committing criminal offenses with the use of explosive devices (Journal of actual problems of jurisprudence, 2019)
In this article, the author raises the problem of conducting a scientifically based analysis of the methods of committing criminal offenses with the help of explosive devices. The author in his article reveals the most common typical ways of committing criminal offenses with the use of explosive devices, classifies them and determines the main characteristics. It can be stated that in modern conditions, law enforcement officers are faced with a clear intensification of the criminal activities of terrorist and extremist organizations, during which various explosive devices are widely used. Accordingly, the issues of countering crimes committed with the use of explosive devices have acquired particular relevance. The question of the study of common methods of committing criminal offenses involving the use of explosive devices has not only scientific-theoretical, but also practical value. The commission of criminal offenses with the use of explosive devices is one of the factors indicating an increased criminalization of society. The development of a set of measures to counter criminal offenses committed with the use of explosive devices is currently one of the promising areas of scientific research, which is predetermined by the increased activity in the world of various terrorist and extremist organizations that actively use explosive devices and explosives in criminal trafficking. Identifying the typical characteristics of the methods of committing various offenses with the use of explosive devices allows you to identify similar actions and with a high degree of confidence to make a conclusion about the involvement of the same persons. Thus, the study of the method of committing a crime committed with the use of an explosive device is necessary for a quick and proper disclosure of a criminal case. Key words: ammunition, explosives, explosive devices, weapons, method of committing a criminal offense.